Evaluasi Psikomotorik Pembelajaran Asmaul Husna melalui Proyek Kaligrafi dalam Pesantren Ramadhan Masjid Al-Fath Seberang Padang - Saputra, Junifer; Remiswal, Remiswal; Khadijah, Khadijah (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the evaluation of the psychomotor domain in Islamic Religious Education, particularly through arts-based project approaches, despite the significant role this domain plays in the internalization of religious values. The objective of this study is to describe the implementation of psychomotor skills assessment in students’ understanding of Asmaul Husna through a calligraphy project conducted during the Pesantren Ramadhan program at Al-Fath Mosque, Seberang Padang. A descriptive qualitative approach was used, with purposive sampling to determine research subjects. Data were collected through observation, interviews, and documentation, and analyzed using thematic analysis techniques. The findings show that psychomotor evaluation was carried out through three main stages: planning, implementation, and follow-up. Assessment was conducted authentically through direct practice and student portfolio work. The results indicate that students were able to integrate religious understanding with artistic expression through calligraphy effectively, reflecting the success of the contextual, project-based learning approach in fostering psychomotor skill development. The implications of this study highlight the importance of innovation in religious education assessment by integrating affective, cognitive, and psychomotor dimensions in a holistic manner.